Framing Comparison of Netanyahu's Denial of the Gaza Famine in Al Jazeera and CNN Arabic - Muhammad Nur; Abdul Basid (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the critical role of media framing in geopolitical conflict by analyzing the coverage of Israeli Prime Minister Benjamin Netanyahu's denial of the Gaza famine, a claim directly contradicted by international humanitarian reports. Employing a qualitative descriptive approach grounded in Robert Entman's framing theory (Problem Definition, Causal Diagnosis, Moral Judgment, and Suggested Remedies), we conducted a comparative analysis of news articles from two ideologically distinct outlets: Al Jazeera Arabic and CNN Arabic. The analysis reveals fundamentally divergent framing strategies. Al Jazeera utilized a decisive Accountability Frame, defining the problem as a "blatant lie" against established humanitarian fact and diagnosing the cause as the "Israeli war of annihilation" and ongoing blockade. Its moral judgment was strongly condemnatory, leading to a proposed political solution (immediate lifting of the siege). Conversely, CNN Arabic adopted a cautious Debate and Juxtaposition Frame, defining the problem as a conflict of high-stakes political claims. It presented an ambiguous causal diagnosis by balancing Netanyahu's denial with counter-data on malnutrition deaths, and implicitly proposed an information solution (transparency and independent journalistic access). This ideological divergence confirms that media alignment dictates narrative construction in highly sensitive conflicts. The findings highlight the significance of discourse linguistics and critical discourse analysis as effective tools for uncovering the hidden agendas and ideological biases embedded in news texts. By analyzing linguistic choices, this research demonstrates how language actively shapes, rather than merely reports, social and political reality.